Anais Do XXVIII Simpósio Brasileiro De Informática Na Educação (SBIE 2017) 2017
DOI: 10.5753/cbie.sbie.2017.213
|View full text |Cite
|
Sign up to set email alerts
|

Recomendação de Objetos de Aprendizagem baseada em Modelos de Estilos de Aprendizagem: Uma Revisão Sistemática da Literatura

Abstract: Abstract. This article presents the results of a Systematic Review of Literature on Recommendation of Learning Objects based on Learning Styles. We selected 49 publications for information extraction. The results show that the most widely used learning style model is Felder and Silverman, highlighting the use of Learning Object Metadata (LOM) as the metadata standard and the specification and management of metadata used as a support mechanism for the recommendation. In the virtual environment aspect, the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
0
6
0
13
Order By: Relevance
“…Neste artigo, o processo foi composto por três etapas, a primeira eliminação baseou-se na leitura conjunta do título, resumo e conclusão, visto que geralmente o título não fornece detalhes suficientes para a avaliação do material. Considerando que a fase de eliminação dos trabalhos envolve a subjetividade do pesquisador, como apontando por [do Nascimento et al 2017], algumas estratégias para guiar o processo foram a definição de critérios de exclusão e de qualidade. Uma medida para verificar se o artigo atendia ou não ao objetivo da pesquisa foi a definição de 06 critérios de qualidade 1 .…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…Neste artigo, o processo foi composto por três etapas, a primeira eliminação baseou-se na leitura conjunta do título, resumo e conclusão, visto que geralmente o título não fornece detalhes suficientes para a avaliação do material. Considerando que a fase de eliminação dos trabalhos envolve a subjetividade do pesquisador, como apontando por [do Nascimento et al 2017], algumas estratégias para guiar o processo foram a definição de critérios de exclusão e de qualidade. Uma medida para verificar se o artigo atendia ou não ao objetivo da pesquisa foi a definição de 06 critérios de qualidade 1 .…”
Section: Metodologiaunclassified
“…As limitações observadas na execução desta RSL são comunsàquelas apontadas por diversos autores na literatura, [Valaski et al 2011], [do Nascimento et al 2017: possíveis decisões subjetivas durante o processo de eliminação dos artigos, tendo em vista a escassez de informações nas publicações.…”
Section: Considerações Finaisunclassified
“…As this is a field that is under study for decades, other works attempting to map and review it have already been done. In [do Nascimento et al 2017] a systematic review of the recommendation of LO based on LS is executed. In their work a total of 49 papers are analyzed and is concluded that FSLSM (Felder & Silvermand Learning Style Model) is the most widely used LS, along with the Learning Object Metadata (LOM) as the metadata standard for the specification and categorization of LO.…”
Section: Related Workmentioning
confidence: 99%
“…Sin embargo, otra cuestión necesaria de estudio es el diagnóstico de los estudiantes en un EVEA donde pueden darse niveles mayores de autenticidad. Se reconoce en la literatura consultada en los últimos años [19]; [20] la importancia del diagnóstico y monitoreo de los estilos de aprendizaje de los estudiantes. A partir del diagnóstico es importante destacar el análisis de los tipos de estrategias didácticas propuestos en la literatura [21]; [22]: centradas en la individualización de la enseñanza, para la enseñanza en grupo, centradas en el trabajo colaborativo, centradas en la presentación y la colaboración.…”
Section: Los Espacios Virtuales De Enseñanza Aprendizaje En El Aunclassified